Ruthenium-nitrosyl complexes as NO-releasing molecules, potential anticancer drugs, and photoswitches based on linkage isomerism. Issue 14 (16th March 2022) - Stepanenko, Iryna; Zalibera, Michal; Schaniel, Dominik; Telser, Joshua; Arion, Vladimir B.
Abstract : The progress in the design and synthesis of ruthenium-nitrosyl complexes, the role of photoinduced linkage isomerization in NO photorelease and possible medical and optical applications are discussed. Abstract : The synthesis of new types of mono- and polynuclear ruthenium nitrosyl complexes is driving progress in the field of NO generation for a variety of applications. Light-induced Ru-NO bond dissociation in solution may involve transient linkage isomers MS1 (Ru-ON) and MS2 (Ru-η 2 -NO), which can be detected spectroscopically and analyzed computationally. The investigation of photoisomerization processes in the solid state may be useful for potential application of such complexes for data storage, photochromic or photomagnetic materials or even non-linear optics. Herein we describe the major developments in the synthesis of ruthenium nitrosyl complexes, their photoinduced linkage isomerization (PLI) processes, their NO release both in the solid state and in solution, and their application as potential anticancer drugs. Illustrative examples of such innovations made mainly in the last decade are provided.